Biomarkers in diagnosis and therapy of oral squamous cell carcinoma: A review of the literature. Issue 5 (May 2017) - Blatt, Sebastian; Krüger, Maximilian; Ziebart, Thomas; Sagheb, Keyvan; Schiegnitz, Eik; Goetze, Elisabeth; Al-Nawas, Bilal; Pabst, Andreas Max
Abstract: Oral squamous cell carcinoma (OSCC) represents the sixth most common cancer, accounting for 2–4% of all malignancies worldwide. The overall survival rate of less than 60% remains generally poor, with prognosis heavily relying on the TNM staging system. Tumor size as well as the presence and extent of lymph node metastases are widely recognized as the most important predictors. However, the underlying mechanisms that lead to an aggressive phenotype are not yet fully understood. Therefore, possible biomarkers are much in need to predict prognosis, to help individualize therapy approaches, and to overcome possible resistance mechanisms. Despite a multitude of recently published biomarkers for OSCC, there is still an ongoing debate regarding their implementation in the clinical workflow. Thus, a systematic literature search via PubMed was performed to update the current literature with the latest evidence. In total, 128 studies were included and over 100 different biomarkers evaluated with reference to their influence of survival, tumor recurrence, advanced grading and lymph node metastasis. In this review, we highlight the important molecular mechanism underlying possible markers in tissue, blood or saliva samples for OSCC. As a major result, no clinical trials could be obtained to prove clinical importance of the validated predictors for survival, tumor recurrence, lymph node metastasis and therapy resistance. Therefore, further clinical investigations are much needed.